2012
DOI: 10.1111/j.1365-2389.2012.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential of NIR spectroscopy to predict soil texture and mineralogy in Cerrado Latosols

Abstract: Near‐infrared reflectance spectroscopy (NIRS) has been accepted as a fast method to evaluate various soil constituents. However, very few studies have used NIRS as a predictor of the textural and mineralogical content of tropical soils. The objective of this study was to investigate the potential use of NIRS as a tool for assessment of diverse soil properties, with specific attention to the prediction of properties related to the mineralogy of a wide range of Latosols from the Cerrado region of central Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 35 publications
5
25
0
4
Order By: Relevance
“…Individualization of soil textural classes by means of spectroscopy at VIS-NIR-SWIR has been observed and reported by various authors and in Brazilian soils, such as Demattê and Garcia [6], Nanni and Demattê [14], Ferraresi et al [45], Vendrame et al [46] and Franceschini et al [36], among others. This individualization was corroborated in our study.…”
Section: Spectroscopic Analyses Of Soil Samplesmentioning
confidence: 84%
See 1 more Smart Citation
“…Individualization of soil textural classes by means of spectroscopy at VIS-NIR-SWIR has been observed and reported by various authors and in Brazilian soils, such as Demattê and Garcia [6], Nanni and Demattê [14], Ferraresi et al [45], Vendrame et al [46] and Franceschini et al [36], among others. This individualization was corroborated in our study.…”
Section: Spectroscopic Analyses Of Soil Samplesmentioning
confidence: 84%
“…Ferraresi et al [45] reached R 2 0.85 for clay content quantification and 0.87 for sand in São Paulo and Goiás States. In regional sampling of Latosols (Ferralsols) of the Brazilian Cerrado, Vendrame et al [46] found 0.83 and 0.74 of R 2 for calibration and validation to determine clay content. In Mato Grosso do Sul State, Franceschini et al [36] obtained satisfactory quantification for clay (R 2 = 0.92 and RPD = 3.59), silt (R 2 = 0.80 and RPD = 2.15) and sand (R 2 = 0.87 and RPD = 2.62).…”
Section: Prediction Models Of Soil Attributesmentioning
confidence: 99%
“…A técnica de espectroscopia de reflectância vem sendo proposta como alternativa para auxiliar os métodos convencionais na determinação de atributos do solo (Madari et al, 2006;Viscarra Rossel et al, 2009;Vendrame et al, 2012). Sousa Junior et al (2011) observaram que a determinação da distribuição granulométrica de uma amostra de solo seco e peneirado, pelo método convencional proposto por Bouyoucos (1962), leva aproximadamente 48 horas, enquanto a mesma determinação feita a partir de informação espectral do solo pelo VIS-NIR-SWIR (do visível e infravermelho próximo ao infravermelho de ondas curtas, 400 a 2.500 nm) leva apenas cerca de 10 min.…”
Section: Introductionunclassified
“…This study seems to confirm that soil type itself does not affect calibrations for total carbon concentrations, but the textural diversity within the sample population used for calibration influences it. The potential of NIRS to predict soil texture and mineralogy in tropical soils have been assessed by other workers (Ferraresi et al, 2012;Vendrame et al, 2012) who describe the development of the calibration models with NIRS and DRIFTS using samples from different soil textures and taxonomies. Such models indicated robustness, since the prediction of amounts of clay, silt and sand leads to a textural classification very similar to the classification obtained from the results of the classical method.…”
Section: Carbon Quantification Using Nirsmentioning
confidence: 99%